A Study of Customer’s Perspicacity about Bank Credit Facilities at NKGSB Cooperative Bank Ltd. (Chinchwad Branch) - Gupta, Dr. Madhulika (International Journal of Psychosocial Rehabilitation, 2020)
A foremostconcern for any organization is how it will fit in debt in its capital structure, simultaneouslythey have to considerthe structure of its equity financing. The company ought to look at its capital structure as a whole and be decisiveon how much capital it requires instantaneously and eventually, and the mixture of equity and debt that it will employ to accomplish those necessities. Credit facilities can absorbnumeroustype of creditsasaccessible for the company as a source of reserve funding. Whereas there are numerouscauses why a company would set up some type of credit facility, the approach is generally a way of generating a backup supply of revenue for different projects. For instance, a company maydecide to issue a bond as a medium of raising money for a particular project. Together withinstituting the bond issue, the companyalso manages a backup line of credit or perhaps a termloan as a backup in the incident that the project be unsuccessful to produce enough revenue to honor the terms of the bond. The study is carried out from January 2019 to April 2019 to understand the customer’s perceptiveness about various credit schemes (Retail Loan)at NKGSB Cooperative Bank Ltd.